Penentuan Anomali Gayaberat Regional dan Residual Menggunakan Filter Gaussian Daerah Mamuju Sulawesi Barat - Karunianto, Adhika Junara; Haryanto, Dwi; Hikmatullah, Fajar; Laesanpura, Agus (EKSPLORIUM, 2017)
Gravity method is a geophysical method that has been frequently used in prospecting mineral resources. The parameter of searched object is based on variations of gravity acceleration measurements on the surface due to variations in sub-surface geological changes. Research area is located in Mamuju Area of West Sulawesi Province where tectonically a complex geological region, which is at a meeting of three large plates, the Pacific plate, the Indo-Australian plate and the Eurasian plate and the smaller Philippine plate. In addition, Mamuju is an area with a high radioactivity dose rate that has potency to radioactive minerals resources. The purpose of the research is to obtain gravity anomalies by using qualitative separation and interpretation of regional and residual gravity anomalies. Complete Bouguer Anomaly (CBA) value of the research area obtained from the measurements was 46.0 – 115.7 mGal. Based on the CBA map, the separation process of regional gravity anomalies and residual using Gaussian filtering technique conducted. This filtering technique works based on spectral analysis of gravity amplitude changes in spatial where the result is a cutoff wave number of 1.1736 x 10-3/meter and a wavelength of 5373.45 m. The regional and residual gravity anomalies range from 51.8 to 102 mGal and -10.4 to 14.8 mGal respectively. The depth of influence of each anomaly is calculated based on their spectral wavelengths, resulting 970.97 m and 100.21 m for regional and residual anomalies respectively. There are five zones based on the residual anomaly map, which are zones A, B, C, D and E. The heaviest positive gravity anomaly is found in zone A and B, which is predicted to be influenced by Adang lava with relative north – south distribution.